The 9th judgment - Patterson, James (b)
Fiction.
Reprint. Originally published: New York : Little, Brown, 2010.
Keywords: Female friendship -- Fiction; Murder -- Investigation -- Fiction; Triangles (Interpersonal relations) -- Fiction